The Speech Acts of Thanking: Pragmatic Strategies Used Among Malay Generation Z (Jurnal Bahasa, 2022)
Generation Z is a generation of technology. They are said to show very little verbal communication skills. They are relatively weak in terms of expression, verbal communication, confidence and interpersonal skills. Among the weaknesses that are commonly mentioned is that the younger generation find it quite "difficult" to express "thank you" in their daily life as it is not considered an important matter. Therefore, this paper aims to examine the strategy of thanking speech acts among the Malay Generation Z. The speech act of thanking expresses feelings of gratitude, appreciation and indebtedness for a gift, offer or help given by a person. This study employs a descriptive quantitative approach in the form of a Discourse Completion Task (DCT) questionnaire. In this approach, counts are performed to indicate which thanking strategies occur more in number and frequency. DCT contains five questions based on three different situations, namely receiving a gift, receiving help and receiving an award. These situations are also differentiated in terms of participant relationships based on social distance and social status. The questionnaire was distributed to 212 respondents representing Generation Z, namely Form 4 and Form 6 students as well as university students. Additionally, the data were analyzed based on a modified version of the classification of gratitude expressions by Cheng (2005), which comprised eight gratitude strategies. The study found that in displaying grateful actions, Generation Z more often used a direct or explicit strategy when using the words "thank you" or "thank you very much". The results also showed that Malay Generation Z is still aware and know how to perform acts of gratitude when faced with situations that require responses of gratitudeKeywords: Verbal communication, speech act, thanking speech act, Generation Z, pragmatics strategies, MalayFull text: PDF